The Role of Montessori Learning Assessment in Early Childhood Education 3-6 years old - Furwanti, Erni; Krismayanti, Yanti; Apriani, Nanin; Listia, Yovita Befi; Sofiah, Yofi Siti (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze the role of assessment in Montessori-based learning for early childhood (aged 3â€“6 years), particularly within the practical life area, and its implications for the development of prosocial behavior. The study is grounded in the issue that early childhood education practices remain largely dominated by conventional, teacher-centered approaches that emphasize academic achievement while providing limited opportunities for fostering childrenâ€™s independence and social skills. In addition, the assessment dimension within Montessori education has not been extensively explored, particularly in relation to authentic assessment practices aligned with childrenâ€™s developmental characteristics. This research employed a qualitative approach with a descriptive design. Data were collected through documentation studies and literature review, supported by secondary data on the Gross Enrollment Rate (GER) of early childhood education in Indonesia from 2021 to 2025. Data analysis was conducted using an interactive model involving data reduction, data display, and conclusion drawing. The validity of the findings was ensured through source and theoretical triangulation. The findings reveal that the implementation of Montessori learning integrated with authentic assessment significantly enhances childrenâ€™s prosocial behavior, including helping, cooperation, sharing, and honesty. There is a clear shift in developmental categories from â€œnot yet developedâ€ and â€œbeginning to developâ€ to â€œdeveloping as expectedâ€ and â€œvery well developedâ€ across all indicators. Authentic assessment conducted through continuous observation enables educators to capture childrenâ€™s development holistically and contextually. Furthermore, concrete activities within the practical life area effectively facilitate the internalization of social values through direct experience.